Efficient metrics and high-level synthesis for dynamically reconfigurable logic. - Meribout, M. (IEEE Transactions on VLSI systems)
The increase in complexity of programmable hardware platforms results in the need to develop efficient high-level synthesis (HLS) tools since it allows more efficient exploration of the design space while predicting the effects of technology specific tools on the design space. Much of the previous works however neglect the delay of interconnects (e.g. multiplexer) which can indeed contribute heavily on the overall performance of the design. In addition, in the case of dynamic reconfigurable logic (DRL) circuits, unless an appropriate design methodology is followed, large number of configurable logic blocks (CLBs) could be used for communication between contexts, rather than for implementing functional units (FUs). The aim of this paper is to present a new technique to perform interconnect-sensitive synthesis, targeting dynamic reconfigurable circuits. Further, the proposed technique exploits multiple hardware contexts to achieve efficient designs. Experimental results on several benchmarks, which have been done on our DRL LSI circuit (Meribout, 2000 and Motomura, 1997), demonstrate that by jointly optimizing the interconnect, communication, and function-unit cost, higher quality designs than other previous techniques (e.g. force-directed scheduling) can be achieved.